2020
DOI: 10.2337/dc19-2550
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Double-Blind Clinical Trial Comparing Ultra Rapid Lispro With Lispro in a Basal-Bolus Regimen in Patients With Type 2 Diabetes: PRONTO-T2D

Abstract: To evaluate the efficacy and safety of ultra rapid lispro (URLi) versus lispro in patients with type 2 diabetes on a basal-bolus insulin regimen. RESEARCH DESIGN AND METHODSThis was a phase 3, treat-to-target, double-blind 26-week study. After an 8-week lead-in to optimize basal insulin glargine or degludec in combination with prandial lispro treatment, patients were randomized to blinded URLi (n 5 336) or lispro (n 5 337) injected 0-2 min prior to meals. Patients could continue metformin and/or a sodium-gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 31 publications
6
44
0
3
Order By: Relevance
“…The PRONTO-T2D study demonstrated that URLi is non-inferior to lispro in terms of change in HbA1c following 26 weeks of treatment and that URLi is superior to lispro at reducing 1-and 2-h PPG excursions during the meal test [21]. In our subpopulation analysis of Japanese patients with T2DM, URLi demonstrated effective glycemic control when used in combination with basal insulin, with an acceptable safety profile.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…The PRONTO-T2D study demonstrated that URLi is non-inferior to lispro in terms of change in HbA1c following 26 weeks of treatment and that URLi is superior to lispro at reducing 1-and 2-h PPG excursions during the meal test [21]. In our subpopulation analysis of Japanese patients with T2DM, URLi demonstrated effective glycemic control when used in combination with basal insulin, with an acceptable safety profile.…”
Section: Discussionmentioning
confidence: 68%
“…The efficacy analysis was conducted as previously described for the overall population [21]. These methods were applied to the Japanese population in a prespecified subset analysis, although statistical power was not taken into consideration, and p values are provided as a reference.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations